Filsafat Pendidikan Pancasila dalam Kurikulum 2013 dan Kurikulum Merdeka: Analisis Komparatif Landasan Filosofis - Winarno Winarno; Heri Santoso; Yuyus Kardiman; Muchtarom (Integralistik, 2026)
Pancasila, as the state foundation and philosophical basis of national education mandated by the National Education System Law Article 2, should serve as an ontological, epistemological, and axiological foundation in every national curriculum. This study aims to analyze and compare the educational philosophy underlying two curriculums and assess the extent to which Pancasila’s educational philosophy is adopted as a philosophical basis. The method used comparative analysis of official curriculum documents, namely Permendikbud No. 57–59 of 2014 (2013 Curriculum) and Permendikbudristek No. 12 of 2024 and Permendikdasmen No. 13 of 2025 (Merdeka Curriculum). The analysis employed thematic content analysis across three dimensions: (1) Philosophical Foundation, (2) Integration of Pancasila, and (3) Philosophical Depth. Results show that the 2013 Curriculum is dominated by progressivism and essentialism philosophies, with partial and normative-moral integration of Pancasila limited to the first three principles. In contrast, the Merdeka Curriculum integrates Pancasila holistically across eight graduate profile dimensions, covering all principles and beginning to engage ontological, epistemological, and axiological levels through a deep learning approach. The Merdeka Curriculum aligns more closely with the idealistic philosophy of Pancasila education than the 2013 Curriculum. The findings imply a need for an explicit philosophical foundation in the curriculum and adequate teacher training so that Pancasila becomes a strong philosophical foundation rather than merely a normative message.